Nonparametric estimation of risk-neutral densities - Maria Grith; Wolfgang Karl Härdle; Melanie Schienle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
This chapter deals with nonparametric estimation of the risk neutral density. We present three different approaches which do not require parametric functional assumptions on the underlying asset price dynamics nor on the distributional form of the risk neutral density. The first estimator is a kernel smoother of the second derivative of call prices, while the second procedure applies kernel type smoothing in the implied volatility domain. In the conceptually different third approach we assume the existence of a stochastic discount factor (pricing kernel) which establishes the risk neutral density conditional on the physical measure of the underlying asset. Via direct series type estimation of the pricing kernel we can derive an estimate of the risk neutral density by solving a constrained optimization problem. The methods are compared using European call option prices. The focus of the presentation is on practical aspects such as appropriate choice of smoothing parameters in order to facilitate the application of the techniques.
Keywords: C13; C14; G12; 330; Risk neutral density; Pricing kernel; Kernel smoothing; Local polynomials; Series methods; Optionspreistheorie; Risikoaversion; Zeitreihenanalyse; Nichtparametrisches Verfahren; Theorie; Schätzung; Deutschland